Assembling the puzzle: pathways of oxytocin signaling in the brain - Grinevich, Valéry; Knobloch-Bollmann, Hanna Sophie; Eliava, Marina; Busnelli, Marta; Chini, Bice (Biological psychiatry, 2016)
Oxytocin (OT) is a neuropeptide, which can be seen to be one of the molecules of the decade due to its profound prosocial effects in nonvertebrate and vertebrate species, including humans. Although OT can be detected in various physiological fluids (blood, saliva, urine, cerebrospinal fluid) and brain tissue, it is unclear whether peripheral and central OT releases match and synergize. Moreover, the pathways of OT delivery to brain regions involved in specific behaviors are far from clear. Here, we discuss the evolutionarily and ontogenetically determined pathways of OT delivery and OT signaling, which orchestrate activity of the mesolimbic social decision-making network. Furthermore, we speculate that both the alteration in OT delivery and OT receptor expression may cause behavioral abnormalities in patients afflicted with psychosocial diseases.